Estimating pass-through rates for the 2022 tax reduction on fuel prices in Germany - Dovern, Jonas; Frank, Johannes; Glas, Alexander; Müller, Lena Sophia; Perico Ortiz, Hector (Energy Economics, 2023)
We analyze the effectiveness of the German tax reduction on fuel prices (`Tankrabatt') that was introduced for three months, starting on 1 June 2022. We use the synthetic difference-in-differences estimator to compare actual retail prices of gasoline and diesel to those in a counterfactual situation without the tax reduction. For gasoline, we find that the tax reduction has been completely passed on to consumers. This result is robust to different approaches of constructing the synthetic control group. For diesel, we find evidence of at least partial pass-through, although the estimates are more sensitive to the employed specification. Moreover, the evidence suggests that pass-through rates for diesel started to decline in August while the tax reduction was still in place. <br
Keywords: fuel; gasoline; diesel; taxes; synthetic control group